GAMBARAN FAKTOR RISIKO LINGKUNGAN FISIK RUMAH PADA KEJADIAN ISPA BALITA DI WILAYAH KERJA UPTD PUSKESMAS BANJARNEGARA 2 TAHUN 2023 - Nida Arifah; Joko Malis Sunarno; Bayu Suseno (Jurnal Ilmiah Medsains, 2023)
Respiratory Infections (ARI) is an endemic disease that affects the upper or lower respiratory tract, usually infectious, a wide spectrum of diseases that range from asymptomatic disease or mild infection to severe and deadly, depending on the causative pathogen, environmental factors and host factors. The purpose of this study was to determine the risk factors of the physical environment of the house on the incidence of ARI in the Working Area of Puskesmas Banjarnegara 2. This study included descriptive research with a cross sectional approach. The population was 139 toddlers and the sample was taken by random sampling as many as 58 toddlers. Data obtained from checklist observation and measurement. The results showed that the density of the house met the requirements as many as 40 (69%) houses, measurement of the temperature of all 58 houses met (100%), measurement of room humidity 35 (60.3%) houses did not meet the requirements, measurement of lighting did not meet the requirements 35 (60.3%) houses, measurement of ventilation 33 (56.9%) houses did not meet, observation of floor conditions mostly met the requirements as many as 54 (93.1%) houses, observation of air contamination mostly did not meet the requirements as many as 52 (89.7%) houses.Based on the results, it is concluded that the influential factors are humidity, lighting, ventilation and air contamination. While house density, temperature, and floor type have no effect on the incidence ofARI.